Sustainable and Dynamic Supply Chain in world Business: Recent Trends - Aakash Sirohi (International Journal of Supply Chain Management, 2022)
By moving from the "integrated" to the "dynamic" supply chain model, businesses may see their supply chains as flexible ecosystems of people, processes, capital assets, technology, and data. In the rapidly evolving corporate world, effective supply chain management (SCM) is a critical issue. Dynamic SCM necessitates good decision information synchronization and integrated decision-making among autonomous chain partners. Complex supply chains (SCs), which are part of globalised economic systems, must be managed to minimize sustainability-related risks and to manage environmental and social impacts in accordance with the expectations of many stakeholders. The analysis of recent trends has highlighted the fact that use of quantitative modelling techniques for sustainable supply chain management (SSCM) is increasingly becoming more and more popular. Secondly, simulation techniques are underrepresented in SSCM compared to analytical models and mathematical programming. For organizations that are looking to infuse a fresh breath in there SCM operations inclusion of system dynamics (SD) modelling for simulating and analyzing complex and dynamic systems as well as for assisting long-term, strategic decision-making will pay rich dividends.Â